A new variety of local realism explains a Bell test experiment: the Theory of Elementary Waves (TEW) with no hidden variables - Boyd, Jeffrey H (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In a recent article on the Theory of Elementary Waves (TEW) (see TEW eliminates Wave Particle Duality in JAP, February 2015), the most controversial aspect was the claim that TEW provides a local realistic explanation of the Alain Aspect 1982 experiment. That claim was not proved. This article fills in that gap by providing a local realistic explanation of a Bell test experiment published in 1998 by Weihs, Jennewein, Simon, et al. Advanced TEW uses no hidden variables, and therefore does not fall under the jurisdiction of Bells theorem. It rejects wave particle duality. It violates the Bell inequalities, yet is local and realistic. Particles follow a bi-ray, which is composed of two elementary rays, traveling at the speed of light in opposite directions, coaxially, conveying no energy. As was the case with the previous article, the main obstacle to credibility is that these assumptions sound incredible. It is wise sometimes to tolerate ridiculous ideas, lest we fail to recognize a paradigm shift when one comes along. Another obstacle to credibility is the multitude of unanswered questions. A truly fruitful theory raises more questions than it answers, by a ratio of 100 to 1. TEW fulfills that definition of fruitfulness.